Conservative management of Cesarean Scar Ectopic Pregnancy - Gupta, Vineeta; Makhija, Amrita; Chaudhari, Priyanka; Tandon, Archna (Indian Journal of Case Reports, 2017)
Caesarean scar pregnancy (CSP) refers to a gestational sac that has implanted in the scar of a previous caesarean delivery due to incomplete healing of the caesarean scar, as may be seen in CSP occurring few months of caesarean delivery. It is the rarest kind of ectopic pregnancy which is usually misdiagnosed leading to life threatening complications, like rupture with haemorrhage and hemodynamic collapse. Therefore, a high index of suspicion is required to diagnose CSP. Here, we present two case reports of CSP presenting at 6 and 7 months after cesarean delivery, respectively. The first one presented to us as a case of incomplete abortion following medical abortion, and the second patient was referred to us as a case of cervical pregnancy. A decrease in the primary caesarean rate and prolongation of the inter-pregnancy interval is essential to avoid CSP.